Correcting intervertebral rotation and scoliosis simultaneously by oblique lumbar interbody fusion: a 3D analysis of EOS images - Xu, Zhongning; Ge, Tenghui; Li, Qingyun; Cai, Ronghui; Wu, Jingye; Sun, Yuqing (Frontiers in Surgery, 2023)
Purpose: With advancements in minimally invasive techniques, oblique lumbar interbody fusion (OLIF) has gained widespread acceptance and is now commonly performed for adult degenerative scoliosis (ADS). The objective of this paper is to evaluate the three-dimensional (3D) intervertebral motions in EOS models before and after surgery, and subsequently assess the efficacy of the 3D correction achieved through staged OLIF. Methods: In this retrospective study, 29 consecutive patients diagnosed with ADS were included, with a mean age of 63.6 years, who underwent staged OLIF surgery between 2018 and 2021. Spinopelvic parameters were assessed using EOS images, and 3D models were reconstructed to measure intervertebral motion angles (IMAs) in 70 surgical intervertebral segments, comprising wedge, lordosis, and axial rotation angles. Regression analysis was conducted to compare IMAs in different planes before and after the staged OLIF surgery. Results: Significant three-dimensional correction was observed in 70 intervertebral segments following the first-stage OLIF. The wedge angles decreased from 5.2°± 4.2°to 2.7°± 2.4° (P < 0.001). The lordosis angles increased from 5.1°± 5.9° to 7.8°± 4.6° (P = 0.014), while the axial rotation angles decreased from 3.8°± 2.6° to 2.3°± 2.1° (P < 0.001). Linear regression analysis revealed a positive correlation between wedge angles and axial angles preoperatively (P < 0.001, r =0.43), as well as between corrected wedge angles and corrected axial angles (P < 0.001, r =0.42). Conclusion: This study demonstrated that intervertebral motions had a correlation between coronal and axial planes in lumbar degenerative scoliosis. First-stage OLIF was competent in correcting segmental scoliosis by inserting cages while correcting rotation deformity simultaneously, as well as improve the sagittal spinopelvic parameters.